DEVELOPING HERBAL TOURISM INNOVATION AS A RELAXION PRODUCT AT TOURIST DESTINATIONS - Tahara Dilla Santi; Manovri Yeni; Radhiah Zakaria; Na’imah; Nabil Shidqi (RADJA PUBLIKA, 2026)
The International Labor Organization (ILO) reports that 2 million people die in the workplace, one of the causes being overexertion. Herbal saunas are decoctions of plants with medicinal properties, including anti-fatigue. Warm steam applied to the skin helps dilate blood vessels, improving circulation. The purpose of this activity was to provide knowledge about various medicinal plants that can be make aromaterapy of candle and used as herbal saunas and to provide community members with skills in making herbal saunas. The PKM method involved participation through outreach and mentoring women in preparing herbal saunas. The activity took place on January 4, 2026, in Nusa Village, with 16 person of LPN The activity began with a pre-test and then a herbal sauna booklet. The results of this activity were an increase in the knowledge and skills of the LPN people, demonstrated by the resulting product, a dried herbal sauna packaged in a standing pouch. Participants were very enthusiastic about the training. The activity concluded with the use of herbal saunas, which were boiled in a steamer and the steam flowed into a portable sauna tent. Participants took turns using the sauna, which had been filled with the herbal sauna decoction.